(3eQBI GdYLGFH aj GdcjejGAs - (3eMeO Hf GdeNJGQ (B( (3GdegJGQ (B)(3, CHh YHO Gddgs
(3ChdgG (B:s
(3CeG HYO aGYdehG ENhGfi ai GdMbjbI CjOce Gddg hEjGi hEjGj bO SeJ geJi HGdYde s
(3BNQgG (B:s
(3hGfJHgJ ef GdefGe aeG COQi CMb Ce CVZGK CMdGe gPG BNQ GdQSGdI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1648s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYI (B190) s
Keywords: (3GdcjejGA h GdWHjYjGJs